INTEGRATION OF ENTREPRENEURSHIP INTO HIGHER EDUCATION (EDUCATIONAL SCIENCES) IN LITHUANIA AND LATVIA: FOCUS ON MODERN PEDAGOGICAL APPROACHES - Melnikova, Julija; Zascerinska, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The purpose of this article is to highlight the aspects of integration of entrepreneurship into higher education (Educational sciences) in Lithuania and Latvia. The article examines the nature of challenges for entrepreneurial teaching and explains how experience-based pedagogies can develop learning environments that replicate aspects of entrepreneurship. The article describes the empiric study, which explored 32 student and 16 university lectures’ opinion on entrepreneurship in Educational sciences. The implications of the article could be useful for university educators, who seek to educate students most effectively with a real intention to become entrepreneurs.